Respuesta :

Answer:

x=3

Step-by-step explanation:

x^2-9

bcos g(-1)=-1

f(g)=x^2+9(-1)=0

x^2-9=0

x^2=9

x=√9

x=3

Answer:

dfgsdfgjfsdpogjpdisfiodfsgjdfgoipgdsfjiojgidfjiogdfjgdosfjoigpdjoigfddhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfk

Explanation:

dfgsdfgjfsdpogjpdisfiodfsgjdfgoipgdsfjiojgidfjiogdfjgdosfjoigpdjoigfddhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdfgsdfgjfsdpogjpdisfiodfsgjdfgoipgdsfjiojgidfjiogdfjgdosfjoigpdjoigfddhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfkdhfguopaszghsdfpgbnhdfijpghsdjfkghdfsghupdssghujidghsdfjgkldfk